Trends and patterns of analgesic utilization in Malaysia from 2010 to 2016: preference for tramadol - Zin, Che Suraya; Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Alias, Nor Elina; Ahmad, Wan Rohaidah; Rani, Nurul Sahida; Ng, Kim Swan; Ye, Felicia Loh (2018)
Introduction Inappropriate or irrational use of analgesics not only leads to increased morbidity and mortality rates and deterioration in quality of life, but can also give rise to misuse of health care resources and increase health care costs.